Performance measurement of logistics processes in project deliveries - Borenius, Stina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The thesis was commissioned by a company operating in the marine and energy markets. The objective of the research was to review the current situation of the logistics processes and measurement of the case company. In addition, the aim was to explore what could be improved related to the logistics processes and performance measurement of the company. Continuous process improvement has been recognised as vital for the success of companies in previous literature. Moreover, especially the logistics process is considered as a significant factor in fulfilling customer expectations. One very useful tool to improve a process is performance measurement. Therefore, the theoretical framework of the thesis addresses literature related to processes and performance measurement, in general and related to logistics in particular. The research was conducted as an intensive case study. The empirical data was gathered mostly by interviews and a questionnaire. All interviewees and questionnaire respondents were employees of the case company. Both quantitative and qualitative data was gathered. The conclusions of the study were made based on both the theoretical review and the empirical data. Currently, there is no consistent logistics performance measurement system at the case company. Thus, one of the findings of the study was that performance measurement related to logistics should be shared more openly. Furthermore, the stakeholders tend to follow logistics performance measurement related only to delivery time. However, it is important to measure performance in a balanced way. Therefore, also other performance indicators should be developed and followed. Especially indicators related to delivery time, delivery quality and delivery costs were emphasized by both previous literature and the stakeholders. Thus, performance indicators especially related to these three should be developed. Moreover, several process elements related to logistics could be improved at the case company. It was also stated that problems may occur before the logistics phase, which affects the work and performance of the logistics department. Recent literature indicates that a shift from a narrow logistics and departmental thinking towards broader supply chain management thinking is to be supported, which could be helpful also for the case company.